2022
DOI: 10.1155/2022/1659860
|View full text |Cite|
|
Sign up to set email alerts
|

Establishment and Evaluation of Influencing Factors and Risk Prediction Model of Severe Neonatal Hyperbilirubinemia Complicated with Acute Bilirubin Encephalopathy

Abstract: Objective. To explore the influencing factors of severe hyperbilirubinemia in neonates complicated with acute bilirubin encephalopathy (ABE) and then build relevant prediction models and evaluate the prediction performance of the models. Methods. The data of 120 neonates with severe hyperbilirubinemia were collected by retrospective analysis. Univariate and multivariate analysis methods were used to analyze the data of 120 children. R software was used to visualize the results of multivariate analysis, and a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Impaired bilirubin metabolism is very common in newborns and may lead to jaundice and yellowing of the skin and other tissues [ 2 , 3 ]. Bilirubin concentrations in the blood above 170 μM might trigger liver and biliary tract dysfunction, even cause irreversible damage to the brain and nervous system [ 4 , 5 ]. Low bilirubin levels indicate iron deficiency (anemia) and may be directly linked to diabetes, coronary heart disease and cardiovascular disease [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Impaired bilirubin metabolism is very common in newborns and may lead to jaundice and yellowing of the skin and other tissues [ 2 , 3 ]. Bilirubin concentrations in the blood above 170 μM might trigger liver and biliary tract dysfunction, even cause irreversible damage to the brain and nervous system [ 4 , 5 ]. Low bilirubin levels indicate iron deficiency (anemia) and may be directly linked to diabetes, coronary heart disease and cardiovascular disease [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%